Answer:
x=-2
Step-by-step explanation:
1/2(2-6x)-4(x+3/2)=-(x-3)+4
(1-3x)-4x-6=-x+3+4
-7x-5=-x+7
Tranpose
-7x+x=5+7
-6x=12
Divide by -6
x=-2
What is the situation from the problem
Answer:
A: 300 B: Malorie
Step-by-step explanation: Katina's account starts at $200 and increases by $20 each month. Malorie starts at only $100 but increases at a rate of $50 per month. for "A", Katina is 4 months in which equals $280. so, you take Malorie's $50 rate times the 4 months and you get $200. You then add that $200 to the starting $100 to equal $300.
B: 50m>20m. Malorie's monthly rate is listed in the equation as $50. Katina's rate of $20 comes from the $20 increase in her account each month.